The effect of interactive nutrition education through Instagram on complementary feeding practices among infants 6-12 months - Nuria Ikhsyania; Cesilia Meti Dwiriani; Lilik Kustiyah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Growth disorders are also common in children. The Health Belief Model (HBM) predicts that maternal perception of child vulnerability to growth disorders motivates adequate feeding practices. Addressing these concerns can effectively drive intervention. This study examined the impact of nutrition education delivered via Instagram on complementary feeding (MPASI) practices in infants aged 6–12 months. This quasi-experimental study was conducted in Bogor City in the year 2024. The sample consisted of 76 breastfeeding mothers, selected using a randomized method. Participants were divided into two groups: the intervention group, which engaged in interactive Instagram discussions after receiving nutrition education (n= 38), and the control group (n= 38), which only received nutrition education. Data were collected through interviews using structured questionnaires. Educational materials were provided twice a week for four weeks via Instagram. The data were analyzed using t-tests. Results: A significant difference (p < 0,05) was observed in the effect of nutrition education delivered via Instagram, both within each group and between groups, in terms of dietary diversity, feeding frequency, and adequacy. In conclusion, interactive education through Instagram has a more significant impact on improving scores in most components of the Health Belief Model (HBM) related to complementary feeding practices.